Emo – kultura fasadowych zainteresowań - Klichowski, Michał (Wydawnictwo Naukowe UAM, 2010)
Artykuł wyjaśnia czym jest kultura Emo. Omówiona została historia tej kultury oraz jej współczesne implikacje. Przedstawiony został także proces budowania fasadowego wizerunku w oparciu o komponenty kultury Emo.

The article explains what the Emo culture is. It discusses the history of this culture and its contemporary implications. It also presents the construction process of the frontal image in support of certain components of Emo culture.
Emo – the culture of frontal interests
Keywords: kultura Emo; Emo culture; zainteresowania; interests; młodzież; young people